2019
DOI: 10.1111/famp.12423
|View full text |Cite
|
Sign up to set email alerts
|

The Family Resilience Inventory: A Culturally Grounded Measure of Current and Family‐of‐Origin Protective Processes in Native American Families

Abstract: The purpose of this article is to introduce the Family Resilience Inventory (FRI) and present findings on initial efforts to validate this measure. The FRI is designed to assess family resilience in one's current family and in one's family of origin, enabling the assessment of family protective factors across these generations. The development of the FRI was the result of many years of ethnographic research with Southeastern Native American tribes; yet, we believe that this scale is applicable to families of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 42 publications
(87 reference statements)
0
47
0
Order By: Relevance
“…Family resilience: Family resilience was assessed through the twentyitem family resilience inventory subscale, a scale of one's current family protective and promotive factors (Burnette et al, 2019), which was created from emergent qualitative results (see Supplementary Appendix B).…”
Section: Methodsmentioning
confidence: 99%
“…Family resilience: Family resilience was assessed through the twentyitem family resilience inventory subscale, a scale of one's current family protective and promotive factors (Burnette et al, 2019), which was created from emergent qualitative results (see Supplementary Appendix B).…”
Section: Methodsmentioning
confidence: 99%
“…Over the years, there has been an increase in the number of studies examining resilience processes and mechanisms that facilitate communities' positive adaptation under challenging circumstances. Studies have identified that people draw strength from their social and cultural networks such as their families to overcome challenges (e.g., Burnette et al, 2019;MacPhee, Lunkenheimer, & Riggs, 2015;Prendergast & MacPhee, 2017). These dynamics, interactions and interrelationships were at the heart of weaving a strong and unique fabric of resilience as families act as a foundation of social and emotional support in times of adversities (Burnette et al, 2019;MacPhee et al, 2015).…”
Section: Semai Family Processes and Functioningmentioning
confidence: 99%
“…Studies have identified that people draw strength from their social and cultural networks such as their families to overcome challenges (e.g., Burnette et al, 2019;MacPhee, Lunkenheimer, & Riggs, 2015;Prendergast & MacPhee, 2017). These dynamics, interactions and interrelationships were at the heart of weaving a strong and unique fabric of resilience as families act as a foundation of social and emotional support in times of adversities (Burnette et al, 2019;MacPhee et al, 2015). Acknowledging the importance of the role of family in studying resilience, further investigation on how one's SEMAI FAMILY PROCESSES & FUNCTIONING 5 cultural ideals and context influence the complex interactions that occur within these networks is required.…”
Section: Semai Family Processes and Functioningmentioning
confidence: 99%
“…Hill-Collins (1997) argues that motherwork refocuses attention on three main themes-(a) survival (the essential work mothers perform to ensure the survival of their children and thus their communities, and its concomitant tolls on mothers), (b) power (mothers' struggle for control of their own bodies and of their children's upbringing, education, and values), and (c) identity (mothers' constant negotiation to constitute their own self-definitions as mothers of color embedded in oppressive systems). Motherwork includes not only caring for one's own children but caring for other children in the community and future generations of children; this more expansive purview of mothering is needed to analyze NA family systems that tend to be characterized by intergenerational extended family and kinship networks (Burnette et al, 2018;Burnette et al, 2019;Tam et al, 2017). NA women's motherwork is better understood when situated in the reproductive justice framework, which highlights the impact of historical and contemporary reproductive and sexual health injustices experienced by NA women (Gurr, 2014).…”
Section: Theoretical Backgroundmentioning
confidence: 99%